Implementing key performance indicators in a Malaysian local government - Hasbolah, Farhana; Mohd Alwi, Norhayati; Mohamad, Muslim Har Sani (Faculty of Economics & Management Universiti Kebangsaan Malaysia, 2012)
Key Performance Indicators (KPIs) is an example of private sector practices developed and implemented in public sector organizations to improve the performance of public services delivery to its optimum level. This paper proposes a case study on one Local Governments (LGs) in Malaysia to investigate the organizational changes through the development and implementation of KPIs. New Institutional Sociology (NIS) under Institutional Theory shall be used to understand the various institutional pressures faced by the organization during the process of developing and implementing KPIs. This study is expected to provide understandings of the whole process of developing and implementing the process-based KPIs in the local government. Hopefully the study will point out new insights to the development of PMS in Malaysian local government from the perspective of NIS.